Improvement of Individual Emotional States and Sounds Production. - Kalmykova, Lyudmila V. (Psychological Prospects Journal, 2017)
The emotional component of the internal picture of speech defect is a manifestation of the mechanisms to control the degree of individual adaptation to the current situation. It depends on how concrete situation is and allows to realize life values of the person and satisfy his needs. As a program of adaptive behavior, the internal picture of the defect is formed under the influence of valuable formations of the person that plays a key role in its formation, including the speech pathology. For optimization the psychological help we need knowledge about the psychological features of persons with peculiarities in speech. The results of contemporary psycholinguistic researches indicate that there are no speech deviations as consequences of intersystem connections while other psychological defects could take place. Together they form complex psychological profile of deviations in mental development, in which structure one of the leading syndromes are the speech peculiarities. In this publication the author reveals the theoretical essence and content, and also practice of psychocorrection work for the improvement of the emotional and mental states of personality with the peculiarities of sounds pronunciation. It has been grounded that exactly this program is a necessary pre-condition for rehabilitation and adaptation of persons with defects of sounds pronunciation.Key words: speech, sounds production, peculiarities of sounds pronunciation, emotional and mental states.